Surfactant toxicity to Artemia Franciscana and the influence of humic acid and chemical composition - Deese, Rachel D. (Environ Chem, 2015)
Surfactants can be extremely toxic to aquatic species and are introduced to the environment in a variety of ways. It is thus important to understand how other environmental constituents, in this case humic acids (HAs), may alter the toxicity of anthropogenic surfactants. Hatching and mortality assays of Artemia Franciscana were performed for three different toxic surfactants: Triton X-100 (Tx-100, non-ionic), cetylpyridinium chloride (CPC, cationic), and sodium dodecyl sulfate (SDS, anionic). Humic acids of varying composition and concentrations were added to the assays to determine the toxicity mitigating ability of the HAs. Tx-100 had a significant toxic effect on Artemia mortality rates and HAs from terrestrial sources were able to mitigate the toxicity, but an aquatic HA did not. CPC and SDS limited hatching success of the Artemia and, as HAs were added, the hatching percentages increased for all HA sources, indicating toxicity mitigation. In order to determine which functional groups within HAs were responsible for the interaction with the surfactants, the HAs were chemically modified by: (i) bleaching to reduce aromatics, (ii) Soxhlet extraction to reduce lipids, and (iii) acid hydrolysis to reduce O- and N-alkyl groups. Although most of the modified HAs had some toxicity mitigating ability for each of the surfactants, there were two notable differences: 1) the lipid-extracted HA did not reduce the toxicity of Tx-100 and 2) the bleached HA had a lower toxicity mitigating ability for CPC than the other modified HAs.